Raman spectrum of the organic–inorganic halide perovskite CH3NH3PbI3 from first principles and high-resolution low-temperature raman measurements - Pérez-Osorio, MA; Lin, Q; Phillips, RT; Milot, RL; Herz, LM; Johnston, MB; Giustino, F (American Chemical Society, 2018)
We investigate the Raman spectrum of the low-temperature orthorhombic phase of the organic-inorganic halide perovskite CH3NH3PbI3, by combining first-principles calculations with high-resolution low-temperature Raman measurements. We find good agreement between theory and experiment and successfully assign each of the Raman peaks to the underlying vibrational modes. In the low-frequency spectral range (below 60 cm-1), we assign the prominent Raman signals at 26, 32, 42, and 49 cm-1to the Pb-I-Pb bending modes with either Agor B2gsymmetry and the signal at 58 cm-1to the librational mode of the organic cation. Owing to their significant intensity, we propose that these peaks can serve as clear markers of the vibrations of the [PbI3]-network and of the CH3NH3+ cations in this perovskite, respectively. In particular, the ratios of the intensities of these peaks might be used to monitor possible deviations from the ideal stoichiometry of CH3NH3PbI3.